PRINCIPAL’S ENTREPRENEURIAL COMPETENCE IN DEVELOPING THE ENTREPRENEURSHIP CLASS AT SD IT MUHAMMADIYAH, BIREUEN REGENCY - Agustina, Agustina; Marsithah, Iis; Khairani, Cut (Universitas Islam Negeri (UIN) Sumatera Utara, 2025)
The purpose of this study is to analyze the planning, implementation, supervision, and evaluation conducted by the school principal in collaboration with stakeholders in developing students' character at SMA IT Assalam Islamic School. This research employed a qualitative method with a descriptive approach. The research subjects consisted of one principal and four teachers. Data collection techniques included interviews, observation, and documentation. The findings reveal that the principal has designed and implemented a collaborative strategy for character development, integrating values such as discipline, honesty, and diligence into both the curriculum and extracurricular activities. The principal also involved parents and the school committee in the execution and supervision of the program, and enforced fair disciplinary policies. While the majority of students demonstrated positive character development, challenges remain in maintaining consistent application of these values. Program evaluations were conducted regularly with stakeholders to improve effectiveness. These findings underscore the importance of synergy among all school elements in fostering sustainable student character development